Sistemi territoriali di socioeconomie locali: il paradigma neorurale come fondamento - Ferraresi, Giorgio (Scienze del Territorio, 2018)
This paper proposes neo-rural paradigm as a key reference in the construction of a “return to local socio-economic systems”. We have already recognised this fundamental role of neo-rurality from the first step (“return to the earth”) of our journey of ‘returns’, in the meeting with a new peasant actorship and its ‘social accomplices’ that expresses a ‘primary’ motion of ‘care and culture’ of the earth. A new beginning that gives life to neo-rural paradigm thus assuming a general value beyond agriculture, extending to all the territorial socio-economies: these are essentially activities for the construction of the Oikos (root of economy and home, that home of human race we call territory). It is above all a matter of giving way on territories to the neo-rural practices that founded that paradigm. Such a work is already under way but it can be extended in the practice of an exchange between disciplinary and experiential knowledge of neo-rural processes, e.g. through local interactive observatories. Experiences that used to be isolated in their ‘internal’ construction, in their ‘pioneering phase’, now raise the issue of their mutual relationship within a “higher-order local”, matrix of their own extensive and cooperating ‘territorial body’. These are already the first founding projects of local systems under construction that reveal features of alternative local geographies towards the ‘agro-urban bioregion’ scenario.